Visual Function Classification System for children with cerebral palsy: development and validation. (10th June 2019) - Baranello, Giovanni; Signorini, Sabrina; Tinelli, Francesca; Guzzetta, Andrea; Pagliano, Emanuela; Rossi, Andrea; Foscan, Maria; Tramacere, Irene; Romeo, Domenico M M; Ricci, Daniela; ,
Abstract : Aim: To develop and validate the Visual Function Classification System (VFCS), which was created to classify how children with cerebral palsy (CP) use visual abilities in daily life. Method: The process of development and validation of the VFCS involved four phases: (1) drafting of the five levels from the analysis of literature and clinical experience; (2) validation of constructs and revision of the levels for concept meaningfulness, using nominal group process; (3) refinement by international Delphi survey; and(4) assessment of interrater reliability among professionals and with caregivers, and of test–retest reliability. Results: Five nominal groups involved 29 participants; 65 people completed the first round and 51 the second round of the Delphi survey. Construct validity was demonstrated within an expert group and external validation through several stakeholders, with the involvement of patients and families to ensure meaningfulness of the concept. Discussions continued until consensus was reached about the construct and content of the five levels. Participants in the reliability study included 29 professionals, 39 parents, and a total sample of 160 children with CP (mean age [SD] 6y 6mo [3y 4mo]; median 5y 7mo, range 1–19y). Absolute interrater agreement among professionals was 86% (weighted κ =0.88; 95% confidence interval [CI] 0.83–0.93). Test–retest reliability was high (weighted κ =0.97; 95% CI 0.95–0.99). Parent–professional interrater reliability on 39 children was moderate (weighted κ =0.51; 95% CI 0.39–0.63). Interpretation: The VFCS has been appropriately constructed and provides a reliable system to classify visual abilities of children with CP both in clinical and in research settings. What this paper adds: The Visual Function Classification System is a valid and reliable system. It classifies visual abilities of children with cerebral palsy in clinical and research settings. At a clinical level, it can be used to harmonize communication among professionals and identify patients' strengths and weaknesses. In research settings, it can be used to stratify patients, define natural history evolution, and interpret intervention studies. What this paper adds: The Visual Function Classification System is a valid and reliable system. It classifies visual abilities of children with cerebral palsy in clinical and research settings. At a clinical level, it can be used to harmonize communication among professionals and identify patients' strengths and weaknesses. In research settings, it can be used to stratify patients, define natural history evolution, and interpret intervention studies. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Rosenbaum on page 14 of this issue. Editor's Choice My Editor's choice for the January 2020 issue is the newly developed Visual Function Classification System (VFCS). This issue features other important papers on vision. I hope the VFCS will usefully complement the existing family of classifications systems for gross motor functioning, manual ability, communication, and eating and drinking in children with cerebral palsy. Resumen: Sistema de clasificación de la función visual para niños con parálisis cerebral: desarrollo y validación: Objetivo: Desarrollar y validar el Sistema de Clasificación de la Función Visual (VFCS, siglas en inglés), que fue creado para clasificar cómo los niños con parálisis cerebral (PC) usan las habilidades visuales en la vida diaria. Método: El proceso de desarrollo y validación del VFCS involucró cuatro fases: (1) elaboración de los cinco niveles a partir del análisis de la literatura y la experiencia clínica; (2) la validación de constructos y la revisión de los niveles para el significado de los conceptos, utilizando un proceso de grupo nominal; (3) refinamiento por encuesta internacional de Delphi; (4) evaluación de la confiabilidad entre evaluadores entre profesionales y con los cuidadores, y de confiabilidad de prueba y reevaluación Resultados: Cinco grupos nominales incluyeron 29 participantes; 65 personas completaron la primera ronda y 51 la segunda ronda de la encuesta de Delphi. La validez de constructo se demostró dentro de un grupo de expertos y una validación externa a través de varias partes interesadas, con la participación de los pacientes y las familias para garantizar el significado del concepto. Las discusiones continuaron hasta que se llegó a un consenso sobre el constructo y el contenido de los cinco niveles. Los participantes en el estudio de confiabilidad incluyeron 29 profesionales, 39 padres y una muestra total de 160 niños con PC (edad media [DS] 6 años 6 meses [3 años 4 meses]; mediana 5 años 7 meses, rango 1‐19 años). El acuerdo de evaluador absoluto entre profesionales fue del 86% ( κ ponderada = 0, 88; intervalo de confianza del 95% [IC] 0, 83‐0, 93). La fiabilidad de Test‐Retest fue alta ( κ ponderada = 0, 97; IC del 95%: 0, 95 a 0, 99). La confiabilidad entre los padres y profesionales entre 39 niños fue moderada (ponderada κ = 0, 51; IC del 95%: 0, 39 a 0, 63). Interpretación: El VFCS se ha construido de manera adecuada y proporciona un sistema confiable para clasificar las habilidades visuales de los niños con PC, tanto en el ámbito clínico como en el de investigación. Resumo: Sistema de Classificação da Função Visual para crianças com paralisia cerebral: desenvolvimento e validação: Objetivo: Desenvolver e validar o Sistema de Classificação da Função Visual (SCFV), que foi criado para classificar como crianças com paralisia cerebral (PC) usam capacidades visuais na vida diária. Método: O processo de desenvolvimento e validação do SCFV envolve quatro fases: (1) rascunho dos cinco níveis a partir da análise da literatura e experiência clínica; (2) validação de construtos e revisão dos níveis de significância dos conceitos, usando processo nominal de grupos; (3) refinamento por meio de levantamento Delphi internacional; (4) avaliação da confiabilidade inter‐examinadores entre profissionais e cuidadores, e confiabilidade teste‐reteste. Resultados: Cinco grupos nominais envolveram 29 participantes; 65 pessoas completaram a primeira rodada e 51 a segunda rodada do levantamento Delphi. A validade de constructo foi demonstrada em um grupo de especialistas, e a validade externa por meio de vários interessados, com envolvimento de pacientes e famílias para assegurar a significância do conceito. As discussões continuaram até que fosse atingido consenso sobre o constructo e o conteúdo dos cinco níveis. Os participantes no estudo de confiabilidade incluíram 29 profissionais, 39 pais e uma amostra total de 160 crianças com PC (média de idade [DP] 6a 6m [3a 4m]; mediana 5a 7m, variação 1–19a). A confiabilidade inter‐examinadores absoluta entre profissionais foi 86% ( κ ponderado=0, 88; intervalo de confiança [IC] a 95% 0, 83–0, 93). A confiabilidade teste‐reteste foi alta ( κ ponderado =0, 97; IC 95% 0, 95–0, 99). A confiabilidade inter‐examinadores pais–profissionais em 39 crianças foi moderada ( κ ponderado =0, 51; IC 95% 0, 39–0, 63). Interpretação: O SCFV foi elaborado apropriadamente e é um sistema confiável para classificar as capacidades visuais de crianças com PC em ambientes clínicos e acadêmicos.